Chemical and biological products used in sugarcane and their effect on Trichogramma galloi - Taguti, Paula Sayuri [UNESP]; Ramalho, Dagmara Gomes [UNESP]; Nascimento, Vinícius Ferraz [UNESP]; dos Santos, Lauany Cavalcante; Taguti, Erica Ayumi [UNESP]; Mihsfeldt, Laila Herta; De Bortoli, Sergio Antonio [UNESP] (Wiley, 2023)
The parasitoid Trichogramma galloi Zucchi (Hymenoptera: Trichogrammatidae) is an effective biocontrol agent of the sugarcane borer, Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae). Its use is often recommended in integrated pest management (IPM) programs in sugarcane. However, the IPM of this crop also involves the use of chemical and biological insecticides, and little is known about the effects of concomitant use of these products together with T. galloi. In this study, we evaluated the effects of the chemical insecticide chlorantraniliprole (Altacor 350 WG) and the biological agents Beauveria bassiana (Bals.-Criv.) Vuill. (Granada WP), Metarhizium anisopliae (Metchnikoff) Sorokin (Opala WP), and Bacillus thuringiensis Berliner var. kurstaki (Dipel WP) on the parasitism of T. galloi adult females against D. saccharalis eggs under laboratory conditions, in addition to biological parameters of the offspring. Treatments with chlorantraniliprole and B. thuringiensis reduced the parasitism rate of T. galloi females. The biological agents M. anisopliae, B. thuringiensis, and chlorantraniliprole increased offspring mortality by more than 30%. The use of B. bassiana favored adult female parasitism rates and did not cause significant offspring mortality. None of the treatments had significant effects on the emergence, longevity, and sex ratio of the offspring. Our results suggest that an insecticide based on B. bassiana can be used concomitantly with the parasitoid T. galloi in sugarcane IPM programs. Moreover, M. anisopliae, B. thuringiensis, and chlorantraniliprole had significant undesirable effects on T. galloi; therefore, they should be used with caution to avoid potential suppression of the parasitoid effect.
Keywords: biocontrol agent; Crambidae; Diatraea saccharalis; entomopathogen; Hymenoptera; insecticide; integrated pest management; IPM; Lepidoptera; parasitoid; sugarcane borer; Trichogrammatidae